Estimation of breaststroke propulsion and resistance-resultant impulses from film analyses - van Tilborgh, L.; Willems, E. J.; Persyn, U. (Swimming Science V, 1988)
In this study, the position of the total body center of gravity (cg) during breaststroke swimming was estimated from film analysis, using a personalized computer model of the human body (adapted from Hanavan, 1964). This allowed for a calculation in each movement phase of the impulses resulting from the difference between propulsion and resistance. Individual variations in a breaststroke movement cycle, which correlated significantly to swimming performance and to hip velocity fluctuation (Persyn, 1974; Persyn, Vervaecke, Thewissen, & Verhetsel, 1981), were then directly related to these resultant impulses. Mainly the new-look, undulating style was anlayzed and compared to the commonly used style of breaststroke swimming.